PERBEDAAN KUALITAS RENDANG DAGING DENGAN PENGGUNAAN BUMBU BASAH DAN BUMBU KERING - Mentari, Berhias; Faridah, Anni; Holinesti, Rahmi; Azhar, Minda (Jurnal Pendidikan Teknologi Kejuruan, 2020)
Beef rendang is a popular traditional food from West Sumatra which is commonly cooked by using fresh seasoning such as herbs and spices yet not all types of those ingredients are effortlessly available to be found. This issue hinders the local community to cook beef rendang with the original taste of West Sumatra. As a matter of fact, producing dried seasoning to cook rendang could be a possible solution to solve this issue. This study aimed to compare the sensory analysis of beef rendang by using fresh and dried seasoning. This sort of research was a pure experiment with a completely randomized design and 3 repetitions. The ingredients being used are beef, coconut milk, chilies, ginger, galingale, lemongrass, shallots, garlic, lime leaves, bay leaves, turmeric leaves and salt, cooking oil, nutmeg and coriander purchased at traditional markets. The seasoning was sautéed and the coconut milk was poured into the pan, then the beef was added onto the coconut milk with the seasoning until it is half cooked in which the name is Kalio (Like curry, but not become rendang yet), then it was heated up and dried up for hours until the coconut milk dried and turned black which is called rendang. In addition, the data collection technique was carried out by giving a questionnaire to the panelists. The data analysis used was the t-test independent sample t-test using SPSS 15.0 software. The results obtained from the research showed that the average values of the sensory evaluation of the two rendang were almost similar. The average values of beef rendang sensory evaluation using fresh and dried seasoning, respectively, were colour 3.26 and 3.53; aroma 4.0 and 4.13; the texture has the same value, namely 3,4; taste namely 4,6 and 4,46 and the hedonic test 4,33 and 4,20. These results were likely identical as what the statistical test attained (t-test) that there are no significant differences between beef rendang using dried seasoning and fresh seasoning for each sensory testing.